GAMBARAN MOTIVASI BELAJAR PESERTA DIDIK SAAT PANDEMI COVID 19 (Studi Kasus pada Peserta Didik Kelas VII SMP N 1 Arjasari yang sedang Belajar dari Rumah karena Pandemi Covid 19) - Kartini, Iis Islami; Rohaeti, Euis Eti; Fatimah, Siti (IKIP Siliwangi, 2020)
Covid 19 is a new virus found in China and has now spread throughout the territory of Indonesia. This incident is certainly very influential for the learning motivation of students because students will feel bored with studying at home. The purpose of this study was to describe the learning motivation of grade VII students at SMP N 1 Arjasari during the Covid-19 pandemic. This research uses descriptive qualitative method which is a case study. The data collection techniques are interviews and documentation. The results showed that the five students at SMP N 1 Arjasari still had motivation of learning with the categories of having student aspirations and aspirations, student abilities, student conditions, and student environmental conditions. Keywords: Covid-19, Motivation of Learning